An evaluation of requirements management and traceability tools - Shahid, Muhammad (2011)
Requirements management is critical to software delivery success and project lifecycle. Requirements management and their traceability provide assistance for many software engineering activities like impact analysis, coverage analysis, requirements validation and regr ession testing. In addition requirements traceability is the recognized component of many software process improvement initiatives. Requirements traceability also helps to control and manage evolution of a software system. This paper aims to provide an evaluation of current requirements management and traceability tools. Management and test managers require an appropriate tool for the software under test. We hope, evaluation identified here will help to select the efficient and effective tool.